Associations Between Mindfulness and Implicit Cognition and Self-Reported Affect - Waters, Andrew J. (Subst Abus, 2009)
Theory suggests that mindful individuals exhibit enhanced attentional processing (e.g., attentional control) and that they maintain a detached perspective to problematic stimuli. For smokers, smoking and affective stimuli are problematic stimuli when they try to quit. In this cross-sectional study, smokers (n = 158) completed 3 modified Stroop tasks (to assess attentional control), 3 Implicit Association Tests (IATs; to assess detached perspective), and a battery of self-report assessments. Degree of mindfulness was negatively associated (P < .05) with self-reported negative affect, perceived stress, and depressive symptom severity, and positively associated (P < .05) with positive affect. Degree of mindfulness was not associated with the ability to disengage attention from smoking or affective stimuli. On the depression IAT, more mindful participants exhibited a more negative IAT effect, suggesting that they may have developed a detached perspective to depression-related stimuli. Theoretical and clinical implications of the data are discussed.